PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN CANVA PADA PEMBELAJARAN IPAS DI KELAS IV SDN 49 KURANJI KOTA PADANG - Hayati, Salimatul; Shilfia Iraqi, Hana; Kharisma, Inggria; Anita, Yesi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low learning outcomes of fourth-grade students at SDN 49 Kuranji Kota Padang in IPAS (Natural and Social Sciences) learning, as evidenced by Mid-Semester Examination results where only 25% of students (7 out of 28) achieved the Learning Objective Achievement Criteria (KKTP) of 75, with a class average of 63.10. This condition was caused by teacher-centered learning, inadequate teaching modules that did not fully meet the Merdeka Curriculum with deep learning approach components, lack of active student involvement, and suboptimal use of learning media and technology. This study generally aimed to describe the improvement of student learning outcomes through the implementation of the Problem Based Learning (PBL) model assisted by Canva in IPAS learning in Class IV SDN 49 Kuranji Kota Padang. This study was a Classroom Action Research (CAR) using qualitative and quantitative approaches, conducted in two cycles with planning, implementation, observation, and reflection procedures. Data collection techniques included tests and non-tests. Research subjects were the classroom teacher and 28 fourth-grade students. The results showed that: (1) teaching module quality increased from 91.66% (Very Good) in Cycle I Meeting 1 to 100% (Very Good) in Cycle II; (2) teacher activity average increased from 89.44% (Good) in Cycle I to 93.77% (Very Good) in Cycle II; (3) student activity average increased from 85.71% (Good) in Cycle I to 92.85% (Very Good) in Cycle II; (4) student learning outcomes in Cycle I obtained an average of 81.04, increasing to 86.48 in Cycle II, with KKTP achievement of 92.86% for attitude, and 100% for both knowledge and skills. It can be concluded that the PBL model assisted by Canva can improve student learning outcomes in IPAS learning in Class IV SDN 49 Kuranji Kota Padang.